Food Spoilage: Detection of Biogenic Amines in Food Samples by Enzyme-based Electrochemical Biosensors - Nurul Hana Masód; Syaza Azhari; Palanivel Sathishkumar (Malaysian Institute of Chemistry (IKM), 2024)
Indexed by Scopus/MyCite